(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This research is aimed to 1) develop an attractive fine art guidebook for making natural material-based collages in the SBdP learning at SDN 42 Kecamatan Hulonthalangi Kota Gorontalo, 2) determine the validity and reliability of the fine art guidebook for making natural material-based collages, and 3) determine the effectiveness of the fine art guidebook for making natural material-based collages for attaining learning objectives. The method used was research and development (R&D) with the 4D developmental stages (Define, Design, Development, and Dissemination). The data collection techniques were using validation questionnaires responded by media design experts and material experts and performing a pilot test at SDN 42 Hulonthalangi Kota Gorontalo. The guidebook for making natural material-based collages acquired a mean score of 83% from material experts, and that being so, was considered ‘very reliable’. Similarly, the media design experts imparted a mean score of 85%, and thereby labeling the guidebook as ‘very reliable’. The results of the pilot tests to lower graders were indicated in the following scores: 82.5% (grade I), 81% (grade II), and 82.2% (grade III).